From "you're fired!" to "let's talk it out" : by negotiationg job terminations, you can improve outcomes for all sides (2013)
Suggests that instituting the negotiation process as a part of job terminations, opens up avenues for the exploration of mutually beneficial tradeoffs, which may promote a smoother transition for both the employee and the organisation.
Keywords: DISMISSAL